Effects of High Doses of Contraceptive Drugs and Their Hormonal Components on Brain Monoamines and Physiological Parameters in Rats - Chentanez, Thyon; Kraipon, Suwadee; Trakulrungsi, Chatchai; Ungsuparkorn, Chutcharin (Journal of Basic and Applied Pharmacology, 2015)
Brain monoamine (5-hydroxytryptamine, 5-HT; dopamine, DA; norepinephrine, NE) concentrations and several physiological parameters were determined in normal diestrous control female rats, ovariectomized rats and female rats treated with high doses of contraceptive drugs or sex steroids for 14 days. Progesterone alone (8 mg/kg/d) or estrogen (0.4 mg/kg/d) plus progesterone (8 mg/kg/d) caused a significant increase in the brain NE concentration. High dose of Neogynon (ethinyl estradiol 20μg/kg/d, d-norgestrel 100 μg/kg/d) caused a significant decrease in the brain 5-HT but not in the brain DA and NE. There was no significant alteration in the brain 5-HT, DA and NE concentration by Microgynon 30 (12 μg/kg/d ethinyl estradiol, 60 μg/kg/d d-norgestrel) The uterine weights were reduced in ovariectomized rats. The ovarian and uterine weights in the ovary-intact rats were increased by high doses of estrogen or estrogen plus progesterone treatment but not with progesterone alone. Neogynon in high dose increased the uterine weight but not the ovarian weight. On the other hand, Depo-provera (60 mg/kg,I.M. single dose) decreased the ovarian weight but not the uterine weight. Combined treatment of estrogen plus progesterone caused significant decrease in rat hematocrit. Ovariectomy for 2 weeks caused significant decrease in the brain protein concentration. Body weight gain was reduced by high doses of estrogen plus progesterone administration but not by other contraceptive drugs used. High dose of estrogen induced mostly estrous appearance of the vaginal smear. Depo-provera, progesterone and Neogynon induced mostly diestrous whereas Microgynon-30 induced mostly metestrous appearance. Effects of treatments used may be both direct and indirect by modifying the hypothalamo-hypophysial-gonadal axis of the intact animals and differences in effects may be caused by differences in dosages and mechanisms of actions of various components in the drugs used.